Knowledge About HIV/Aids with Compliance To Provider Initiated Testing and Counseling In 1st Trimester Pregnant Women - Ni Made Ayu Wulandari; Lina Darmayanti Bainuan; Sabrina Farani (Syntax Corporation, 2022)
Human Immunodeficiency Virus-Aquaired Immunodeficiency syndrom (HIV-AIDS) was one of disease that got special attention from the health world. The research was based on a large number of mothers still do not understand deeply about HIV/AIDS and do not follow PITC (Provider Initiated Testing and Counceling) so as not to be detected early possibility of the risk of transmission of HIV/AIDS from mother to baby. The purpose of this research was to know the correlation of knowledge about HIV/AIDS with the compliance to Provider From Testing And Counseling (PITC) on 1st trimester of pregnant women. The design used in this study was analytic approach with cross sectional correlation. The population in this research was all 1st trimester pregnant women in PPM (Private Practice Midwife) Mrs